GAYA BAHASA SLOGAN IKLAN ROKOK DI TELEVISI - Adam, Mohamad Riski; Pakasi, Jenny Hilda; Kalangi, Leika M V. (Kajian Linguistik, 2019)
This research aims to have a descriptive of the types of cigarette’s slogans by using qualitative descriptive method. The data collected in this study were taken from the slogans which could be found in television. Furthermore the data were analyzed by using language style theory and semantic to reveal the types of language style and the meaning behind the slogans. After being analyzed, the data then classified based on the types of language style and meaning found in the slogans. The study showed that, in total there were 11 slogans that were analyzed, which consisted of three metaphors, two hyperboles, two ellipses, two repetitions, one alliteration and one litotes. The semantic meaning to analyzed this language style is conceptual meaning.Keywords : language style, slogan, cigarette’s advertisement